2017
DOI: 10.15694/mep.2017.000188
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years of Night Medicine In Graduate Medical Education

Abstract: Residency programs are arduous and rigorously structured surrounding active patient care management. Residency years are formative years for physician's career. Gaining trust and autonomy from supervising physicians for their actions is critical to be an effective team member and gaining clinical experience and education. . Entrusting a resident with critical actions and behaviors shapes their competency and judgments. Becoming a competent practicing physician requires clinical problem solving and judgment dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The right balance between learner autonomy and supervision is ideal for critical thinking and self-reflection [ 22 ]. When learners are given autonomy, they are motivated to be accountable for the patient, an attitude that is vital in effective clinical practice [ 23 ]. Studies of students given autonomy revealed an associated increase in intrinsic motivation, as well as a desire to learn and take on challenges [ 18 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The right balance between learner autonomy and supervision is ideal for critical thinking and self-reflection [ 22 ]. When learners are given autonomy, they are motivated to be accountable for the patient, an attitude that is vital in effective clinical practice [ 23 ]. Studies of students given autonomy revealed an associated increase in intrinsic motivation, as well as a desire to learn and take on challenges [ 18 ].…”
Section: Reviewmentioning
confidence: 99%
“…Patient care should always be prioritized, and supervising attendings should “adjust their level of supervision”, depending on the level of urgency for critical action and trainee competence [ 20 ]. Therefore, residency programs ideally should have a balance between trust, accountability, and autonomy while still prioritizing patient care and safety [ 23 ].…”
Section: Reviewmentioning
confidence: 99%